2012
DOI: 10.1128/aac.05315-11
|View full text |Cite
|
Sign up to set email alerts
|

Emergence of OXA-48-Type Carbapenemase-Producing Enterobacteriaceae in German Hospitals

Abstract: h Nine carbapenem-resistant Enterobacteriaceae isolates collected from eight patients in five German hospitals were investigated. Six isolates produced the OXA-48 carbapenemase, and three isolates produced OXA-162, which is a point mutant form of OXA-48. Both carbapenemase genes were located on IncL/M-type conjugative plasmids. Insertion sequence IS1999 (truncated or not by IS1R) was located upstream of the bla OXA-48 and bla OXA-162 genes in all of the isolates. Pulsed-field gel electrophoresis typing indicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

3
49
0
5

Year Published

2012
2012
2024
2024

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 81 publications
(57 citation statements)
references
References 19 publications
3
49
0
5
Order By: Relevance
“…In the past decade, bla IMP-8 -producing K. pneumoniae isolates have been reported in Taiwan (8,9,14). Previous studies have reported that carbapenemases (bla KPC , bla , and bla OXA-162 ) could be found in R. planticola, R. ornithinolytica, and other Enterobacteriaceae (2,5,6,9,15). The carbapenemase genes in R. planticola in any specific country can be found in carbapenem-resistant Enterobacteriaceae, especially K. pneumoniae, in that country (Table 2).…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…In the past decade, bla IMP-8 -producing K. pneumoniae isolates have been reported in Taiwan (8,9,14). Previous studies have reported that carbapenemases (bla KPC , bla , and bla OXA-162 ) could be found in R. planticola, R. ornithinolytica, and other Enterobacteriaceae (2,5,6,9,15). The carbapenemase genes in R. planticola in any specific country can be found in carbapenem-resistant Enterobacteriaceae, especially K. pneumoniae, in that country (Table 2).…”
mentioning
confidence: 99%
“…Bacteremia was the most common clinical manifestation in six of the 11 R. planticola infection cases in the literature (3). To date, there are isolates of Raoultella ornithinolytica and R. planticola which are resistant to carbapenem and carry different carbapenemases, including bla KPC , bla , and bla OXA-162 genes (2,5,6). However, bla IMP-8 -producing R. planticola has not been reported in the literature.…”
mentioning
confidence: 99%
“…OXA-48 carbapenemase is an Ambler class D ␤-lactamase that was first identified in 2001 from a multidrug-resistant Klebsiella pneumoniae isolate from Turkey (7). Many sporadic cases have been reported, first in Turkey and then in many other European countries and Israel (8)(9)(10)(11)(12)(13). OXA-48 is now considered an endemic carbapenemase in Enterobacteriaceae, at least in Turkey and in North African countries such as Morocco, Algeria, and Tunisia, and a source of outbreak situations in France, Belgium, Spain, and the Netherlands (14)(15)(16)(17)(18)(19)(20).…”
mentioning
confidence: 99%
“…The MICs of ceftazidime and meropenem were determined by the broth dilution method (22). The group included 113 isolates producing KPC-(n ϭ 21), VIM-(n ϭ 44), NDM-(n ϭ 24), IMP-(n ϭ 4), and OXA-48-type (n ϭ 19) carbapenemases and one isolate coproducing VIM and IMP metallo-␤-lactamases (23)(24)(25)(26)(27)(28)(29). The remaining 48 isolates were non-carbapenemase producers (Table 1) (21,30).…”
mentioning
confidence: 99%